Not every graph is connected : ¬(every graph is connected)
: ¬(∀x( Graph(x)⟹ Connected(x))) (option a)
Now we can simplify above expression as below , ¬(∀x( ¬Graph(x)∨ Connected(x)))
Now bringing negation inside,we get ∃x( Graph(x)∧¬ Connected(x)) (option b)
now apply double negation to the above statement as it does not change its meaning (law of double negation)..
¬ ¬ (∃x( Graph(x)∧¬ Connected(x)))
now applying inner negation to all terms we get :¬∀x(¬ Graph(x)∨ Connected(x)) (option c)
Therefore option a,b,c are equivalent ..